Flaxseed oligosaccharides alleviate DSS-induced colitis through modulation of gut microbiota and repair of the intestinal barrier in mice. Issue 9 (28th August 2020) - Xu, Zhenxia; Chen, Wenchao; Deng, Qianchun; Huang, Qingde; Wang, Xu; Yang, Chen; Huang, Fenghong
Abstract : Intestinal epithelial barrier dysfunction with dysbiosis of gut microbiota contributes to the occurrence and acceleration of colitis. Abstract : Intestinal epithelial barrier dysfunction with dysbiosis of gut microbiota contributes to the occurrence and acceleration of colitis. This study aimed to evaluate the effect of flaxseed oligosaccharides (FOSs) on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) mice and to elucidate the underlying mechanisms. UC was induced in mice by administering 2% DSS in drinking water for 8 days. Then, FOS (50 mg kg −1 d −1, 100 mg kg −1 d −1 and 200 mg kg −1 d −1 ) was administered by gavage for 14 days. The results showed that FOS treatment (200 mg kg −1 d −1 ) significantly ameliorated colitis by decreasing disease activity index (DAI), increasing colon length and improving colonic histology. FOS treatment (200 mg kg −1 d −1 ) down-regulated the critical markers of oxidative stresses, including malondialdehyde (MDA) and myeloperoxidase (MPO). Furthermore, FOS (200 mg kg −1 d −1 ) significantly suppressed the levels of pro-inflammatory cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-6 and interleukin (IL)-1β but increased that of anti-inflammatory cytokine interleukin (IL)-10. The 16S rDNA gene high-throughput sequencing results indicated that FOS treatment increased the gut microbial diversity and inhibited the proliferation of inflammation-related bacteria such as unidentified_Clostridiales . An increase in total short-chain fatty acids (SCFAs), propionic acid and butyric acid, was also observed by FOS supplementation. FOS (200 mg kg −1 d −1 ) also protected the intestinal barrier by increasing the protein levels of Claudin1 and Occludin. In conclusion, FOS attenuated DSS-induced colitis by modulating the gut microbiota and repairing the intestinal barrier.